Fatal Road Traffic Accidents: Causes and Factors Responsible - Singh, Harnam; Kushwaha, Vinita; Agarwal, A D; Sandhu , S S (Journal of Indian Academy of Forensic Medicine, 2016)
Road traffic accidents are one of the leading causes of morbidity and mortality in the world. The  etiological factors may be classified into human and environmental out of which human factor account for  90% of the accidents. The present study was conducted to know the causes and factors responsible for  the accidents. Human error is responsible for accidents in 77% of cases in which drivers were at fault in  56.2% of cases followed by pedestrians and passengers of vehicles responsible for 17.8 and 3.0% cases  respectively. Defects in vehicles, poor weather accounted for accidents in 8.4% cases respectively and  bad roads were responsible for accidents in 4% cases only. None of the driver or passenger of the  vehicles was wearing helmets or seatbelts, a very disturbing trend. The important human factors  responsible for accidents were, over speeding, rash driving, not following traffic rules, carelessness while  crossing roads, playing on road, alcohol intake, fatigue and sleepiness.
Keywords: Road traffic accidents; Causes; Risk factors; Drivers; Human error